KHOTBAH EKSPOSITORI YANG KEKINIAN - Ferdinand Lisaldy,; Gernaida. K. R Pakpahan; Tony Suhartono (JURNAL IMPARTA, 2024)
Expository preaching is a type of sermon that is considered to promote biblical validity and inerrancy. In accordance with the Bible's doctrine of inerrancy, the Bible's texts regarding past truths should also be applied to us in the 21st century. This means that a biblical text that was acknowledged as true in the past should still be relevant to be applied today. To bring it to the present, the meaning and intent of writing a biblical text must first be captured by the expositor. Therefore, this study attempts to explore various writings on expository sermons, how they are structured, and how they are delivered from various sources in a descriptive way, then compiles a practical argument regarding current expository sermons. The preparation of an expository sermon involves exegesis in the form of in-depth research on the verses to be preached, the use of various research aids such as Bible commentaries, lexicons, Bible dictionaries, encyclopedias, and other tools. Furthermore, the results of that study can be compiled into an expository sermon. The next step is the hermeneutic task, to adapt it to the needs of the congregation today. The last step is how the preacher then uses the art of rhetoric with a variety of communication skills to be able to send a Biblical message according to the listeners and their current needs. The whole process is aimed at delivering sermons that are Biblical, but up to date.